Divergent response profile in activated cord blood T cells from first‐born child implies birth‐order‐associated in utero immune programming. Issue 3 (2nd December 2015) - Kragh, M.; Larsen, J. M.; Thysen, A. H.; Rasmussen, M. A.; Wolsk, H. M.; Bisgaard, H.; Brix, S.
Abstract: Background: First‐born children are at higher risk of developing a range of immune‐mediated diseases. The underlying mechanism of 'birth‐order effects' on disease risk is largely unknown, but in utero programming of the child's immune system may play a role. Objective: We studied the association between birth order and the functional response of stimulated cord blood T cells. Method: Purified cord blood T cells were polyclonally activated with anti‐CD3‐/anti‐CD28‐coated beads in a subgroup of 28 children enrolled in the COPSAC2010 birth cohort. Expression levels of seven activation markers on helper and cytotoxic T cells as well as the percentage of CD4 + CD25 + T cells were assessed by flow cytometry. Production of IFN‐γ, TNF‐α, IL‐17, IL‐4, IL‐5, IL‐13, and IL‐10 was measured in the supernatants. Results: IL‐10 secretion ( P = 0.007) and CD25 expression on CD4 + helper T cells ( P = 0.0003) in the activated cord blood T cells were selectively reduced in first‐born children, while the percentage of circulating CD4 + CD25 + cord blood T cells was independent of birth order. Conclusion: First‐born infants display a reduced anti‐inflammatory profile in T cells at birth. This possible in utero 'birth‐order' T‐cell programming may contribute to later development of immune‐mediated diseases by increasing overall immune reactivity in first‐born children as compared to younger siblings.